The effects of resistance training voluntary to failure on muscle mass and strength in overweight men / Basil Imran Khairulanwar … [et al.] - Khairulanwar, Basil Imran; Kamaruddin, Harris Kamal; Abu Bakar, Al-Hafiz; Gray, Stuart; Mohd Aznan, Ellail Ain; Jamaludin, Masshera; Ismail, Ahmad Dzulkarnain (Universiti Teknologi MARA, Perlis, 2023)
Skeletal muscle has an often-underappreciated role in health, with low muscle strength being linked with increased risk of a range of poor health outcomes such as diabetes, cardiovascular disease, cancer, and respiratory disease mortality. Recently, if exercise is performed voluntary to failure, then gains in muscle mass and strength are similar regardless of the load at which exercise is performed. This study aimed to examine the effects of three days per week of resistance training voluntary to failure on muscle adaptations in overweight men consisting of one set of eight exercises. A total of 10 overweight men were recruited for this study. Each exercise was performed based on 80% of 1-RM voluntary to failure and lasted around 30 minutes. The 1-RM test and body composition tests were performed during the baseline and post-intervention. The three sessions per week for six weeks of resistance training of one set per eight exercises to voluntary failure resulted in an increment of 2.3% in muscle mass, and 25.5% in muscle strength. Other than that, a 4.9% reduction in body fat percentage was also observed in this study. It could be concluded that six weeks of three-session resistance training per week voluntary to failure results in an improvement in muscle strength, muscle mass, and reduction of body fat percentage in overweight men.